Prevalence of depression in Type 1 diabetes and the problem of over‐diagnosis. Issue 11 (5th January 2016) - Fisher, L.; Hessler, D. M.; Polonsky, W. H.; Masharani, U.; Peters, A. L.; Blumer, I.; Strycker, L. A.
Abstract: Aims: To determine the prevalence of depression and diabetes distress in adults with Type 1 diabetes and the rate of false‐positives when compared with rates of major depressive disorder. Methods: The sample consisted of 368 individuals with Type 1 diabetes, aged> 19 years. Individuals completed: the eight‐item Patient Health Questionnaire depression scale (PHQ8), which was coded using four scoring criteria (scores> 10, > 12 and> 15, and Diagnostic and Statistical Manual of Mental Disorders 5 (DSM) algorithm scores); the Type 1 Diabetes Distress Scale; and the Structured Clinical Interview for DSM Disorders (SCID) to assess major depressive disorder. Results: The prevalence rates of depression according to the eight‐item Patient Health Questionnaire were: score> 10, 11.4%; score> 12, 7.1%; score> 15, 3.8%; and positive algorithm result, 4.6%. The prevalence of major depressive disorder was 3.5%; and the prevalence of at least moderate diabetes distress was 42.1%. Depending on the criterion used, the false‐positive rate when using the Patient Health Questionnaire compared with the results when using the SCID varied from 52 to 71%. Of those classified as depressed on the PHQ‐8 or Structured Clinical Interview for DSM Disorders, between 92.3 and 96.2% also reported elevated diabetes distress. No significant association was found between any group classed as having depression according to the PHQ8 or the SCID and HbA1c concentration. Depression was significantly associated with more other life stress, more complications and a lower level of education. Conclusions: We found an unexpectedly low rate of current depression and major depressive disorder in this diverse sample of adults with Type 1 diabetes, and a very high rate of false‐positive results using the Patient Health Questionnaire. Considering the high prevalence of diabetes distress, much of what has been considered depression in adults with Type 1 diabetes may be attributed to the emotional distress associated with managing a demanding chronic disease and other life stressors and not necessarily to underlying psychopathology. What's new?: The prevalence of current depression in adults with Type 1 diabetes is far lower than commonly assumed, and is similar to rates reported in community populations. There are high rates of false‐positive results when comparing the eight‐iterm Patient Health Questionnaire and structured diagnostic interviews to identify major depressive disorder. The prevalence of significant diabetes distress is high among adults with Type 1 diabetes, ˜40%. Much of what self‐report depression scales, such as the Patient Health Questionnaire, assess is not psychopathology but, instead, is the emotional distress associated with managing a demanding chronic disease over time. The findings of this study permit more targeted interventions directed at the emotional side of diabetes.